A qualitative study on the impacts of COVID-19 on the delivery of randomised controlled trials evaluating lay-delivered psychological interventions in five countries - Alessandro Massazza; Bayard Roberts; Daniela C. Fuhr; Aniek Woodward; A-La Park; Egbert Sondorp; David McDaid (SSM - Mental Health, 2023)
COVID-19 is having substantial impacts on research conduct, including clinical trials. However, there is limited research investigating the impact of the pandemic on the conduct of clinical trials and barriers to the delivery of interventions. The current study contributes to filling this gap by investigating the impacts of COVID-19 and related mitigation strategies in the context of five randomised controlled trials (RCTs) of lay-delivered psychological interventions for Syrian refugees in Jordan, Lebanon, the Netherlands, Switzerland, and Turkey. We conducted semi-structured interviews with purposively selected researchers (N = 14) across all five countries. Data were analysed using codebook thematic analysis. The trial researchers highlighted how COVID-19 has had pervasive impacts across different components of the trial including recruitment, assessment, intervention delivery, and supervision. These impacts were considered to influence the external and internal scientific validity of these trials, as well as some aspects of trial administration such as budgeting and the workforce. Various mitigation strategies to adapt to constraints imposed by pandemic responses were described by researchers, such as shifting to a remote intervention delivery and evaluation or adding COVID-19 measures to better understand the impacts of COVID-19 on outcome data. The current piece provides an account of the impacts of COVID-19 on the conduct of trials of lay-delivered psychological interventions for refugees in five countries. Our findings will be valuable for researchers testing similar interventions during COVID-19 and other public health emergencies.